Proinflammatory chemokine CXCL14 activates MAS-related G protein-coupled receptor MRGPRX2 and its putative mouse ortholog MRGPRB2 - Ghazl Al Hamwi; Vigneshwaran Namasivayam; Beatriz Büschbell; Robin Gedschold; Stefan Gölz; Christa E. Müller (2024)
Abstract Patients with idiopathic pulmonary fibrosis show a strongly upregulated expression of chemokine CXCL14, whose target is still unknown. Screening of CXCL14 in a panel of human G protein-coupled receptors (GPCRs) revealed its potent and selective activation of the orphan MAS-related GPCR X2 (MRGPRX2). This receptor is expressed on mast cells and − like CXCL14 − upregulated in bronchial inflammation. CXCL14 induces robust activation of MRGPRX2 and its putative mouse ortholog MRGPRB2 in G protein-dependent and β -arrestin recruitment assays that is blocked by a selective MRGPRX2/B2 antagonist. Truncation combined with mutagenesis and computational studies identified the pharmacophoric sequence of CXCL14 and its presumed interaction with the receptor. Intriguingly, C-terminal domain sequences of CXCL14 consisting of 4 to 11 amino acids display similar or increased potency and efficacy compared to the full CXCL14 sequence (77 amino acids). These results provide a rational basis for the future development of potential idiopathic pulmonary fibrosis therapies.